2021
DOI: 10.1101/2021.03.05.434071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Procollagen C-Proteinase Enhancer 1 (PCPE-1) is a marker of myocardial fibrosis and impaired cardiac function in a murine model of pressure overload

Abstract: Aims: Procollagen C-proteinase enhancer 1 (PCPE-1) is an extracellular matrix protein and a major regulator of fibrillar collagen biosynthesis. Previous work has shown that its abundance is often increased in the context of tissue repair and fibrosis. The present study was designed to evaluate its potential as a biomarker of myocardial interstitial fibrosis (MIF), a well-established pathogenic pathway leading to heart failure. Methods and Results: Cardiac fibrosis was induced in rats using an optimized model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…In the fibrotic diaphragms of the mdx mice collected at 4 and 8.5 months of age, there was an overall increase in PCPE-1, detected by immunoblotting and immunofluorescence, which was not quantified but seemed to follow the marked increase in collagen I [125] . Notably and similarly to the observations made in models of cardiac and liver fibrosis [100] , [113] , [125] , PCPE-1 and collagen I were also co-localized in diaphragm tissue. Finally, this study showed that the elevation of PCPE-1 levels in mdx mouse plasma was comparable to that observed for the N-propeptide of collagen III (PIIINP), an established marker of fibrosis [145] .…”
Section: Involvement Of Pcpe-1 In Tissue Repair and Fibrosissupporting
confidence: 84%
See 4 more Smart Citations
“…In the fibrotic diaphragms of the mdx mice collected at 4 and 8.5 months of age, there was an overall increase in PCPE-1, detected by immunoblotting and immunofluorescence, which was not quantified but seemed to follow the marked increase in collagen I [125] . Notably and similarly to the observations made in models of cardiac and liver fibrosis [100] , [113] , [125] , PCPE-1 and collagen I were also co-localized in diaphragm tissue. Finally, this study showed that the elevation of PCPE-1 levels in mdx mouse plasma was comparable to that observed for the N-propeptide of collagen III (PIIINP), an established marker of fibrosis [145] .…”
Section: Involvement Of Pcpe-1 In Tissue Repair and Fibrosissupporting
confidence: 84%
“…It was also co-localized with fibrotic areas in the myocardium. Notably, both in this study and in the model of MI described above, there was an excellent correlation between the PCPE-1 protein quantified in the heart by immunoblotting and the amount of collagen I measured through immunoblotting or Sirius Red staining (r = 0.82 and 0.92) [100] , [113] .…”
Section: Involvement Of Pcpe-1 In Tissue Repair and Fibrosissupporting
confidence: 61%
See 3 more Smart Citations